FORMS OF CULTURAL ACTIVITY AT THE TIME OF SIGNIFICANT SOCIAL CHALLENGES: TO THE RESULTS OF THE ХІХ INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE AT THE RIVNE STATE HUMANITARIAN UNIVERSITY - Vytkalov, Serhii (Ukrainian Cultural Studies, 2023)
The essence and professional orientation of such events as a scientific conference is revealed, its role in stimulating scientific research is emphasized, the "thematic repertoire" of the topics applied for participation in the 19th International Scientific and Practical Conference "Ukrainian and World Culture in the Conditions of Globalization Challenges and War" is analyzed reports, the leading directions of researchers' scientific research are clarified, the most characteristic topics of speeches, announced for discussion and submitted for publication are emphasized; the importance of the specified form of publicizing the results at the time of significant social transformations and war is emphasized. Emphasis is placed on the importance of conducting similar events during the period of changes in the value orientations of society and the importance of creating various forms of consolidation of scientific and pedagogical workers of the country's higher education institutions at the time of complex social transformations and challenges is pointed out.
Keywords: artistic creativity; conference; foreign cultural experience; cultural practices; educational and cultural space; eurointegration; international scientific communication